Conceptual Mapping of Formative Research in the Peruvian University - Turpo-Gebera, Osbaldo; Diaz-Zavala, Rocío; Gutiérrez-Aguilar, Olger; Mango-Quispe , Pedro; Gutiérrez-Salcedo, Eduardo Luis (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
Formative research is an educational method that involves individuals in their own research-based learning. This study explores the development and perspectives of formative research in Peruvian universities through the analysis of postgraduate thesis reports. Using conceptual mapping as an analytical method, key concepts, categories, and conceptual distinctions are identified, revealing the landscape of formative research and its challenges in the Peruvian university context. The increasing emergence of studies on this topic in various fields of professional and academic training is highlighted, focusing on clarifying its notions, characteristics, and applications.